West European Communist Parties after the Revolutions of 1989
XXV, 233 p.
Keywords: This book analyses the impact of the collapse of communism in Eastern Europe and the former Soviet Union on the Communist Parties of Western Europe. Seven case-studies, covering the Italian, French, Spanish, Portuguese, Belgian, British and German parties, provide a tightly-argued comparative perspective. The conclusion assesses the range of responses to the dramatic events of 1989-91 and likely future direction of the west European communist movement. It is argued that, whilst it is no longer possible to talk of a coherent 'family' of communist parties, various individual parties - some of them in revised form - may continue to prosper.